Evaluation of the Infectious Potential of Neoparamoeba perurans Following Freshwater Bathing Treatments - Richard S. Taylor; Joel Slinger; Chris Stratford; Megan Rigby; James W. Wynne (Microorganisms, 2021)
Freshwater bathing for 2–3 h is the main treatment to control amoebic gill disease of marine-farmed Atlantic salmon. Recent in vitro studies have demonstrated that amoebae (Neoparamoeba perurans) detach when exposed to freshwater and that some eventually reattach to culture plates when returned to seawater. Here, we evaluated the potential for gill-detached N. perurans to survive a commercially relevant treatment and infect AGD-naïve fish and whether holding used bathwater for up to 6 h post treatment would lower infectivity. AGD-affected fish were bathed in freshwater for 2 h. Naïve salmon were exposed to aliquots of the used bathwater after 2, 4, 6 and 8 h. The inoculation was performed at 30 ppt for 2 h, followed by gradual dilution with seawater. Sampling at 20 days post inoculation (dpi) and 40 dpi confirmed rapid AGD development in fish inoculated in 2 h used bathwater, but a slower AGD development following exposure to 4 h bathwater. AGD signs were variable and reduced following longer bathwater holding times. These results suggest that viable amoebae are likely returned to seawater following commercial freshwater treatments, but that the risk of infection can be reduced by retention of bathwater before release.